Street children, criminological research and emotional labour: reflections from the field - Atkinson-Sheppard, Sally (Fieldwork experiences in criminology and security studies, 2023)
The chapter considers the involvement of street children in criminological research by drawing on a 3-year case study in Dhaka, Bangladesh. The chapter reflects on the need to develop and utilise emotional labour as a key methodological tool for conducting research into crime and violence. The chapter discusses the emotional labour utilised at 3 stages of the research process: before, during and after the completion of the study. I conclude by reflecting on the importance of emotional labour to engage participants, facilitate the research process and develop reflexivity. These reflections relate specifically to developing a more nuanced understanding of the victim–offender dichotomy, rooted within wider notions of constructions of childhood, and coloniality and my own positionality as a British scholar conducting research in Bangladesh.